Lâm Đồng thực hiện chính sách phát triển kinh tế - xã hội vùng dân tộc thiểu số từ 2003 - 2008 - Trần, Thị Thúy Nga (Trường Đại học Đà Lạt, 2012)
Lam Dong is aprovice south Highlands with 40 ethnic group. Despite economic difficulties but also many of Lam Dong provice has focused on economic development - society for ethnic minorities. As a result, the 2008 ethnic life impooved significantly.